The Use of Technology in EFL Assement Process at a Vocational High School in Samarinda - Endra Sufanlay; Iwan Setiawan; Yuni Utami Asih; Bibit Suhatmady (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2025)
This study investigates the integration of technology in the English as a Foreign Language (EFL) assessment process at a Vocational High School in Samarinda. Although the role of technology in education is increasing, its application in EFL assessment is still minimal in this context. Using a qualitative approach, data were collected through interviews involving EFL teachers. There are three research questions underlying this study, the first is what are technology tools used in the EFL assessment process in a Vocational High School in Samarinda? the second is How is the technology used by the English Teachers of a Vocational High School in Samarinda? and the last is, What are the challenges in using technology for the EFL assessment process? This study reveals that English teachers at a Vocational High School in Samarinda have integrated various technological tools in EFL assessment, especially post-distance learning due to the COVID-19 pandemic. Tools such as Google Forms, Duolingo, Google Classroom, Quizizz, and Kahoot are widely used although most teachers have only acquired these skills through self-learning. The stages carried out by teachers in using digital technology tools in the assessment process are first preparation and drafting of online exam questions, second online assessment strategies and methods, third fraud monitoring and prevention, and finally exam materials and topics. The main challenges faced include limited internet access, unstable Wi-Fi networks in schools, and students' low digital literacy on the platforms used. Nevertheless, teachers are adapting and working towards effective assessment.